Efficient Technique for PAPR and BER Reduction in Downlink Large Scale MU-MIMO-OFDM System - Singh, Jagtar; Kedia, Deepak (International Journal of Sensors Wireless Communications and Control, 2021)
Background & Objective: The Orthogonal Frequency Division Multiplexing (OFDM) based large scale multiuser multiple input multiple output (LS-MU-MIMO) system is a preferred choice for signal transmission because it can substantially enhance the spectral and energy efficiency of the next-generation wireless systems. However, there are several practical issues in implementing large multiuser-MIMO-OFDM systems and one of the critical issues is the high Peak-to-Average- Power Ratio (PAPR). Due to the use of a large number of antennas at the Base Station (BS) of an LSMU- MIMO-OFDM system, it requires a large number of Power Amplifiers (PAs) which are needed to be connected to each antenna element. The high PAPR in an OFDM based LS-MU-MIMO system results in the decrease in the efficiency of PAs and enhancement in nonlinear signal distortions. This work is concerned with the reduction in PAPR of LS-MU-MIMO-OFDM systems using the SCFDMA scheme for the downlink transmission. The reduction in PAPR is achieved on the basis of discrete Fourier transform spreading (DFT-S) scheme known as DFT-SC-FDMA. The SC-FDMA scheme can achieve the reduction in PAPR of MIMO-OFDM signal up to the level of single-carrier transmission. Further, the reduction in PAPR is achieved with the sub mapping schemes such as localized FDMA (LFDMA) and distributed FDMA (DFDMA), Interleaved FDMA (IFDMA). Results: In this work, we propose to perform jointly multiuser MMSE precoding, SC-IFDMA and antenna reservation technique to reduce the PAPR and Bit Error Rate (BER) of the large MU-MIMO system. To show the effectiveness of the proposed scheme in the reduction of PAPR with different modulation techniques, subcarriers, and subcarrier mapping schemes, the results are compared with the existing OFDM based large MU-MIMO system. Conclusion: The MATLAB simulation results confirm that our proposed combination of MMSE MUprecoding, SC-IFDMA and antenna reservation technique is able to reduce PAPR and BER to a significant extent for LS-MU-MIMO-OFDM systems.
Keywords: BER